Proudhon, o los principios de autoridad y libertad. Breve introducción a la teoría del sistema federal (Andamios, Revista de Investigación Social, 2011)
Through the Principle of Authority and the Principle of Freedom, Proudhon guides us into the master principles of the Theory of the Federal System, which he considers the most appropriate to deal with political centralization of the State and economic monopoly, being at once capable of maintaining “unity in diversity”. In the light of the contemporary problems, Proudhon’s proposals on decentralization of political power and on direct economic action, as opposed to political and economic absolutism, confer to his thinking a pulsating topicality, and make it a substantial reference to build a viable alternative to the growing contemporary State and corporate centralism.
Keywords: Principle of Authority; Principle of Freedom; Federal System; political contract; agricultural-industrial federation